Comparison of two methods for malondialdehyde measurement - Al-Fawaeir, Saad; Özgür Akgül, E.; Çayci, Tuncer; Demirin, Hilmi; Kurt, Yasemin Gülcan; Aydin, Ibrahim; Erbil, M. Kemal (Derman Medical Publishing, 2011)
Aim In this study, we aimed to measure malondialdehyde levels by two different methods and compare these methods. Material and Methods Serum malondialdehyde levels of 60 volunteers were measured with thiobarbituric acid test and high pressure liquid chromatography after derivatization of malondialdehyde with 2,4 dinitrophenylhydrazine and these two methods were compared. Results A statistically significant difference (p<0.001) has been found in serum malondialdehyde levels measured by high pressure liquid chromatography (1.85±0.09 ?mol/L) and spectrophotometry (2.47±0.18 ?mol/L). Cohesion between measurements made by two different methods have been evaluated and the interclass correlation coefficient has been found as 0.365 (p=0.042). Statistically significant, weak-mild degree correlation has been found between measurements (r=0.284, p=0.028). Conclusions High pressure liquid chromatography method for malondialdehyde measurement after derivatization with 2,4 dinitrophenylhydrazine provided a more accurate and sensitive assessment of lipid peroxidation than the conventional spectrophotometric thiobarbituric acid method.
Malondialdehid Ölçümünde iki Yöntemin Karşılaştırılması
Keywords: High Pressure Liquid Chromatography; Lipid Peroxidation; Malondialdehide; Oxidative Stress; Spectrophotometric Method